Semantic service discovery in heterogeneous cyber-physical systems - Andreas Lober; Hartwig Baumgärtel; Richard Verbeet (Data Science and Innovation in Supply Chain Management: How Data Transforms the Value Chain. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 29, 2020)
Purpose: A primary requirement of Industry 4.0 and realization of Cyber-Physical Systems in production and logistics is the dynamic connection of physical and digital components. Service-oriented Architectures are a well established approach to meet this requirement. However, a service discovery using syntactic descriptions of services limits efficient application of a Service-oriented Architecture concerning the complexity and variability of existing processes. Methodology: A semantics based mechanism for service discovery can solve this limitation. It uses an ontology management system containing a domain specific ontology and modelling specific Cyber-Physical Systems as individuals. SPARQL Protocol And RDF Query Language (SPARQL) queries searching this ontology with context-related parameters. A use case demonstrates the mechanism by realizing an in-house transport request. Findings: A syntax based service discovery requires a definition and publishing of unique service names. However, complex Cyber-Physical Systems using multiple parameters during service calls require disproportionate effort to implement and maintain these names. A semantics based service discovery considers various parameters by using a specific ontology calling services by their properties without knowing the service name. Originality: A semantics based is decoupled from specific service implementations of components in a Cyber-Physical Systems. Therefore, an explicit specification of parameter configurations in service descriptions is not necessary. A Service-oriented Architecture can be implemented in complex systems without extensive adjustments or coordination mechanisms.
urn:nbn:de:gbv:830-882.0115101; hdl:10419/228914; https://econpapers.repec.org/RePEc:zbw:hiclpr:29
Keywords: 650; Logistics; Industry 4.0; Digitalization; Innovation; Supply Chain Management; Artificial Intelligence; Data Science